2018
DOI: 10.17079/jkgn.2018.20.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moral Sensitivity and Nursing Practice Environment in Person-centered Care in Long-term Care Hospital Nurses

Abstract: The aim of this study was to examine effects of moral sensitivity and nursing practice environment on person-centered care by nurses in long-term care hospitals. Methods: Participants in this study were 118 nurses, with a least 4 months experience working in a long-term care hospital in Daegu City or North Gyeongsang Province. Data were collected from March 17 to 28, 2017 using questionnaires about general characteristics, the Korean Version Person-centered Care Assessment Tool, the Korean Moral Sensitivity Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
5
9
0
6
Order By: Relevance
“…Nurses with more positive perceptions of the work environ- In addition, nurses who reported higher levels of personcentered care tended to perceive more positive perceptions about the nursing practice environment (r=0.27, P=0.007) and greater self-leadership (r=0.40, P<0.001). These findings are consistent with previous evidence that the work environment or nursing practice (e.g., organizational structure and teamwork for nursing practice) are related to autonomous activities and compassion of nurses, which are essential components for person-centered care [10,13,19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nurses with more positive perceptions of the work environ- In addition, nurses who reported higher levels of personcentered care tended to perceive more positive perceptions about the nursing practice environment (r=0.27, P=0.007) and greater self-leadership (r=0.40, P<0.001). These findings are consistent with previous evidence that the work environment or nursing practice (e.g., organizational structure and teamwork for nursing practice) are related to autonomous activities and compassion of nurses, which are essential components for person-centered care [10,13,19].…”
Section: Discussionsupporting
confidence: 92%
“…These findings emphasize the critical significance of a supportive environment for nursing practice and self-leadership to improve person-centered care, as highlighted by previous results from various nursing units (e.g., in internal medicine or surgical units of tertiary hospitals, the ICU, or the emergency room) [10,19,23,26]. Furthermore, this study indicates that the nursing practice environment and self-leadership are essential determinants of person-centered care in oncology nurses, who have multiple responsibilities in caring for cancer patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The clinical learning environment was the last factor affecting PCCC; thus, supporting previous studies that showed a significant correlation between PCCC and the environment [46][47][48]. We, thus, infer that supportive cultures should be maintained through the establishment of mutually cooperative relationships among many interacting clinical professionals, such as clinical practice professors, practice instructors, and heads of institutions.…”
Section: Discussionsupporting
confidence: 85%
“…도덕 적 민감성은 실제 상황에서 도덕적 문제의 존재를 인식할 수 있는 능력 (Lutzen & Nordin, 1994) (Jo & Kim, 2013) (Do & Kang, 2019). 또한 요양병원 간호사의 도덕적 민감성이 인간 중심 돌봄에 유의한 영향을 주는 변수였다 (Park, 2017). 간호학에서 '돌봄'은 의학과 간호학을 구별하는 요소로 간 호제공자가 가져야 할 구체적 행위이다 (Watson, 2006 .…”
unclassified